Composition operators on Banach function spaces - de Jager, Pierre (Department of Mathematics and Applied Mathematics, 2014)
The aim of this thesis is to provide a survey of the topic of composition operators on spaces of (equivalence classes of) measurable functions and attempt to unify some of the most important results contained in the literature. A large class of these spaces can be equipped with norms turning them into Banach lattices. These spaces are called Banach function spaces and examples include the Lebesgue, Lorentz, Orlicz and Orlicz-Lorentz spaces.